STRATEGI PROMOSI PERUMAHAN JAYA IMPERIAL PARK TANGERANG UNTUK MENARIK KONSUMEN BARU - Febrianto, Eko (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2023)
This research examines the promotion strategy applied by PT Jaya Garden Polis in marketing Jaya Imperial Park housing to the public. Researcher is interested to raise the theme of this research because PT Jaya Garden Polis with its products Jaya Imperial Park which is a new product in the midst of competition in Regency area can survive in the marketing of housing products among property developers. It demonstrated by the intense promotion competition carried out by the developers through the use of various media campaigns both intensively and extensively and Jaya Imperial Park is present again as an existing market share. The promotional strategies undertaken by Jaya Imperial Park are by Advertising, Sales Promotion, and Mouth to the Mouth to introduce, market and attract new customers. The purpose of this study is to find out the promotional strategies used Jaya Imperial Park housing to attract new consumers and to find out what media are used in promoting it. This study uses qualitative research methods that describe how promotional strategies and media campaigns which have been used by Jaya Imperial Park. Where the data collection stage using primary data through interviews and observation, then secondary data through intermediary media in the form of archives, documents, and photos from Jaya Imperial Park. The results of this study reveal that the promotional strategy which was run is to use the elements of promotion mix through Advertising, Sales Promotion, and Mouth to the Mouth by carrying out events that play a role in introducing, marketing, and attract new customers to be inhabited in housing Jaya Imperial Park.